Characterization of calcium-containing phases in alkali-activated municipal solid waste incineration bottom ash binder through chemical extraction and deconvoluted Fourier transform infrared spectra - Zhu, Weiping (2020)
It has been reported that municipal solid waste incineration bottom ash (IBA) can be a potential precursor for alkali-activated materials (AAM). This study investigates chemical composition and structure of calcium-containing phases in an alkali-activated IBA (AA-IBA) binder by a novel combination of selective chemical extraction and Fourier transform infrared (FTIR) spectral subtraction and deconvolution. Salicylic acid/methanol extraction is used to isolate the calcium-containing phases from the AA-IBA binder. X-ray powder diffraction and FTIR spectroscopy are used for sample characterization. Spectral subtraction is carried out to assign FTIR peaks of calcium-containing phases and deconvolution is used to discover various individual Si-O peaks hidden in the single broad FTIR peak. Results show that the AA-IBA consists of about 20 wt.% calcium silicate hydrate (C-S-H) and pirssonite (Na2Ca(CO3)2·2H2O). Chemical structure of the C-S-H in AA-IBA is found to be broadly similar to that in aged Portland cement paste, with possibly a higher degree of polymerization of the silicate chains. The methodology established in this study is significant and can greatly benefit the development of sustainable construction materials because many industry by-products and solid wastes are Si and/or Al rich, which could be potential AAM precursor.